Effects of Millet Bran Dietary Fiber and Millet Flour on Dough Development, Steamed Bread Quality, and Digestion In Vitro - Yunlong Li; Jing Lv; Lei Wang; Yingying Zhu; Ruiling Shen (Applied Sciences, 2020)
Twenty-five percent of steamed millet flour (MF) and different contents of dietary fiber (DF) were added to wheat flour (WF). The results showed that 25% of steamed MF and DF had significant effects (p < 0.05) on dough farinographical and tensile properties. With the increase of DF content, the hardness of the steamed bread increased, the elasticity decreased significantly, and the sensory acceptability decreased. The results of digestion showed that the content of rapidly digested starch (RDS) and slowly digested starch (SDS) in MF steamed bread decreased with the increase of DF, while resistant starch (RS) increased. Meanwhile, the starch hydrolysis rate, hydrolysis index (HI), and glycemic index (GI) decreased significantly (p < 0.05), and protein digestibility decreased gradually. Comprehensive evaluation showed that the 2% DF sample had good sensory performance and medium GI, which is beneficial to the control of blood sugar levels. These good functional properties could meet the requirements of a healthy diet.